Endometrial adenomyoma polyp caused postmenopausal bleeding mimicking uterine malignancy - Ci Huang; Mun-Kun Hong; Dah-Ching Ding (Gynecology and Minimally Invasive Therapy, 2017)
This case report presents a 66-year-old postmenopausal woman with a case of endometrial adenomyomatous polyp (EAP) that presented as postmenopausal vaginal bleeding and mimicked endometrial cancer. The ultrasonography revealed a mildly enlarged uterus approximately 7.1 cm × 3.7 cm in size. The endometrium was 1.9 cm in diameter. The findings of magnetic resonance image (MRI) comprised abnormal intrauterine lesions with multiloculated cystic components. Endometrial biopsy by Pipelle was performed, and revealed hematoma. The hysteroscopy was then arranged, and two polypoid tumors were found. Tumor resection was performed, and the histology of the tumor was adenomyoma. EAP is a rare benign tumor of the uterus that is not easy to differentiate from endometrial cancer by ultrasound or MRI. Hysteroscopy is recommended when the results of tissue sampling by Pipelle differ from the image findings.